2007
DOI: 10.1089/thy.2006.0012
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Cancer Tissue Expresses High Level of Type 1 5′-Deiodinase

Abstract: Type 1 5'-deiodinase is one of two isoenzymes that participate in conversion of prohormone thyroxine into triiodothyronine (T3). A decrease in type 1 5'-deiodinase expression was observed in renal clear cell carcinoma, thyroid cancer, and lung cancer. The aim of this study was to evaluate type 1 5'-deiodinase activity and mRNA level in breast cancer tissue and non-cancerous surrounding breast tissue. Material was collected from 36 patients undergoing radical mastectomy or local tumor resection. In all non-canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Interestingly, previous studies found that altered expression and activity of DIOs is present in several models of heart failure, brain injury, tumor tissues and local inflammation [43,44,45,46]. These findings support the hypothesis that SNPs in DIOs may play an important role in the development of CD.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, previous studies found that altered expression and activity of DIOs is present in several models of heart failure, brain injury, tumor tissues and local inflammation [43,44,45,46]. These findings support the hypothesis that SNPs in DIOs may play an important role in the development of CD.…”
Section: Discussionsupporting
confidence: 69%
“…It is also known that thyroid hormone receptors bind to an estrogen response element of target gene promoters, which affects the estrogen-dependent gene transcription (29). A study on breast cancer cell lines have revealed that the thyroid hormone stimulates cell growth and division in the ER-positive MCF-7 cell line (30). This highlights that the thyroid hormone is clearly associated with the expression of the three DIOs; therefore explaining their overexpression in the MCF-7 cells observed in the present study.…”
Section: Rt-qpcr Evaluations On Human Breast Cancer and Non-cancerousmentioning
confidence: 99%
“…It supplies a large portion of circulating plasma T 3 , it also acts as a scavenging enzyme removing inactive iodothyronines and recycling iodine, as well as playing a part in thyronamine biosynthesis [66,67,68]. Studies have also shown DIO activity associated with local inflammation and tumoural tissues [69,70]. DIO1 as a selenoprotein has also been discovered to be protective against iodine deficiency when its activity is reduced with selenium deficiency.…”
Section: Discussionmentioning
confidence: 99%